A PROSPECTIVE OBSERVATIONAL STUDY ON DISTRIBUTION PATTERN OF ADVERSE EFFECTS OF BRONCHODILATORS AMONG BRONCHIAL ASTHMA AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE PATIENTS IN A TERTIARY CARE TEACHING HOSPITAL IN A RURAL AREA OF KANCHEEPURAM DISTRICT - K, KEERTHANA; SOMU, LAVAKUMAR; VISHWAMBHAR (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The objectives of the study were (i) to study the distribution pattern of adverse effects of bronchodilators at initiation or during the course of therapy, (ii) to make a causality assessment of adverse effect identified using the WHO adverse drug reaction (ADR) probability scale, and (iii) to identify next drug tolerated better by him/her. Materials and Methods: This is an observational study that lasted for duration of 2 months. Inclusion Criteria: All patients reporting ADR after initiation of bronchodilator or during the course of bronchodilator therapy for bronchial asthma/ chronic obstructive pulmonary disease within the study period were included in the study. The suspected adverse effect was noted and documented. Causality assessment based on the WHO scale was employed. Results: During the study period, ten patients reported to have ADR for bronchodilators were identified and the WHO Causality Scale for ADR was applied and the better drug tolerated by the patient was noted. Conclusion: Inhalational forms of longer acting beta-2 agonists were better compliable to the patients with no observable adverse effects.